2009
DOI: 10.1007/s10916-009-9356-8
|View full text |Cite
|
Sign up to set email alerts
|

Heart Monitoring Garments Using Textile Electrodes for Healthcare Applications

Abstract: We measured the electrical activity signals of the heart through vital signs monitoring garments that have textile electrodes in conductive yarns while the subject is in stable and dynamic motion conditions. To measure the electrical activity signals of the heart during daily activities, four types of monitoring garment were proposed. Two experiments were carried out as follows: the first experiment sought to discover which garment led to the least displacement of the textile electrode from its originally inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…Classic ECG monitoring requires that the patient remain stationary in the supine position and is thus not conducive to continuous ambulatory monitoring. Wearable Holter devices facilitate long-term and ambulatory monitoring of general wellness, sport, sleep, and numerous heart irregularities, often providing data for heart rate variability analyses [18,19,39].…”
Section: Current Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Classic ECG monitoring requires that the patient remain stationary in the supine position and is thus not conducive to continuous ambulatory monitoring. Wearable Holter devices facilitate long-term and ambulatory monitoring of general wellness, sport, sleep, and numerous heart irregularities, often providing data for heart rate variability analyses [18,19,39].…”
Section: Current Practicementioning
confidence: 99%
“…The authors compared different weaves and concluded that woven electrodes with a reduced number of conductive warp yarns and conductive paste between connections provide the best signal-to-noise ratio. In contrast, Cho et al [19] investigated several different garment designs to decrease motion artifact of ECG electrodes in a knit shirt, relying on the convex shape of the embroidered electrodes and the proximity of the electrodes to the body as facilitated by the stretchable knit. Their different garment designs involved lines of less elastic fabric (8% polyurethane vs. 20% in the rest of the garment) in various configurations to stabilize the shirt.…”
Section: Active Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cho et al [22] have developed four slevless shirts with different so called cutting lines over the ECG sensor. The cutting lines's function was to provide extra stability in the garment near the sensor but also in the directions in which the sensor might be dislocated during movement.…”
Section: Electrode Placement/displacementmentioning
confidence: 99%
“…While research on contact-type sensors has generally been conducted based on the principle of electrical resistance or piezoelectricity, investigations of noncontact-type sensors have mostly focused on the capacitive methods [5][6][7][8]. In research on noncontact type sensing, the magnetic-induced sensing method has recently emerged [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%